Amelioration of hypercalcemia by cinacalcet treatment in a subject with relapsing acquired hypocalciuric hypercalcemia: A case report. Issue 42 (22nd October 2021) - Sanada, Junpei; Kamei, Shinji; Shimoda, Masashi; Tatsumi, Fuminori; Kimura, Tomohiko; Obata, Atsushi; Kohara, Kenji; Nakanishi, Shuhei; Kaku, Kohei; Mune, Tomoatsu; Kaneto, Hideaki
Abstract: Rationale: Hypocalciuric hypercalcemia is classified as acquired hypocalciuric hypercalcemia (AHH) and familial hypocalciuric hypercalcemia (FHH). While FHH is inherited as an autosomal dominant trait, AHH is one of the rare acquired diseases and is usually treated with prednisolone. Here, we report a case with relapsing AHH which was well controlled with cinacalcet therapy. Patient concern: A 68-year-old Japanese man was referred to our institution because of hypercalcemia. Despite such hypercalcemia, he was almost asymptomatic. Diagnostics: We diagnosed him as AHH due to the following reason. First, the ratio of calcium (Ca)/creatinine clearance was very low which met the criteria. Second, there was no overt family history of hypercalcemia. Third, his serum Ca level was within the normal range 3 years before. Fourth, despite hypercalcemia, he was almost asymptomatic and had no evidence of primary hyperparathyroidism. Interventions: Although it is known that steroid therapy is useful for AHH, optimal treatment remains unknown and cinacalcet therapy is very much limited for the treatment of AHH. In this subject, we introduced cinacalcet therapy for the treatment of relapsing AHH. Outcomes: Serum Ca and parathyroid hormone levels were normalized after such therapy with cinacalcet. Conclusions: We should bear in mind that cinacalcet treatment is effective for the treatment of relapsing AHH.